2018
DOI: 10.1634/theoncologist.2017-0602
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Serum VEGF in Neoadjuvant Chemotherapy for Patients with Triple-Negative Breast Cancer: A New Strategy for Early Prediction of Treatment Response and Patient Survival

Abstract: Neoadjuvant chemotherapy (NAC) followed by definitive surgery is a standard of care for locally advanced breast cancer. The identification of sensitive responders to neoadjuvant therapy is highly significant for breast cancer, especially triple-negative breast cancer (TNBC). Results of this study indicate that the monitoring of serum vascular endothelial growth factor (VEGF) could identify patients with favorable or poor responses at an early time point of NAC. Furthermore, the prediction power of VEGF was bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…VEGFs are also involved in tumour cell migration as regulators of BC proliferation and tumour cell escape from apoptotic signals. This characteristic makes VEGFs a potential target candidate in BC patients in the neoadjuvant setting [93]. Arai et al [94] suggested that VEGFs also play an essential role in trastuzumab therapy by minimising the allocation of tumour cells to the lymphatic vessels in HER2-positive BC.…”
Section: Tumour Cell Intravasationmentioning
confidence: 99%
“…VEGFs are also involved in tumour cell migration as regulators of BC proliferation and tumour cell escape from apoptotic signals. This characteristic makes VEGFs a potential target candidate in BC patients in the neoadjuvant setting [93]. Arai et al [94] suggested that VEGFs also play an essential role in trastuzumab therapy by minimising the allocation of tumour cells to the lymphatic vessels in HER2-positive BC.…”
Section: Tumour Cell Intravasationmentioning
confidence: 99%
“…A correlation between VEGF and shorter relapse-free and overall survival in breast cancer patients have been reported previously [27]. In TNBC, Wang et al reported that monitoring serum VEGF can be an early predictor of response to treatment and patients' survival [28].…”
Section: Discussionmentioning
confidence: 64%
“…49 Serum MMP-9, VEGF and secreted protein acidic and rich in cysteine (SPARC) were promising biomarkers to predict responses to NAC and prognosis of TNBC patients. 51,52 miRNA Alternation…”
Section: Small Molecular Changes With the Use Of Nac Changes In Subtypesmentioning
confidence: 99%